Liquid Gating Meniscus‐Shaped Deformable Magnetoelastic Membranes with Self‐Driven Regulation of Gas/Liquid Release (Adv. Mater. 3/2022). Issue 3 (21st January 2022) - Liu, Jing; Xu, Xue; Lei, Yi; Zhang, Mengchuang; Sheng, Zhizhi; Wang, Huimeng; Cao, Min; Zhang, Jian; Hou, Xu
Abstract : Liquid Gating Liquid‐gating technology is attracting increasing attention for the delivery of some brand‐new properties for real‐world applications. In article number 2107327, Xu Hou and co‐workers report a self‐driven smart liquid‐gating system, developed by designing a liquid‐gating magnetoelastic porous membrane with reversible meniscus‐shaped deformations. This system provides a universal and convenient way to realize active regulation of gas/liquid release. The illustrated visible gas/liquid‐mixture content monitoring showcases one example of the application of the reported material.